Farmers’ attitude to the effectiveness of ICTs Use in their Farming, Nay Pyi Taw, Myanmar - Win, Naing Kyi; Htwe, Nyein Nyein (Advances in Social Sciences Research Journal, 2020)
This study focused on farmers’ attitudes to the effectiveness of ICTs in their farming and farmers’ challenges in accessing it. Extension workers of the respective Townships identified the 144 sample farmers, and the data was collected through interviews using questionnaires during 2019. There were frequency means and a dichotomous scale used to analyze the ICT attitude pattern among farmers and a 5-point Likert scale with the options. This study explored the personal factors of ICT accessed farmers who are significantly getting young and middle age, high school, and graduate-level education and a moderate working experience compared with ICTs non- access farmers. 110 out of 144 farmers frequently used and accessed ICTs such as Radio, FM radio, TV, Facebook, Phone, and Agricultural Journals to obtain the agricultural information, but 34 farmers could not access ICTs due to the high cost, other social factors, and low ICT exposure. Most of the farmers received agricultural information from related Departments and Organizations traditionally, such as training, meeting, demonstration, trials, and conferences. More than half of the farmers were positively consistent agricultural information with their needs, but the rest did not meet their needs. Most farmers believed highly positive to agricultural information. However, some farmers responded negatively to agricultural details because they seem commonly knowledgeable information. Farmers mentioned in this study that more than half of farmers positively showed that attitude on high true and true regarding agricultural information. Moreover, farmers encountered insufficient electricity, challenging ICT exposure, low trust, and social problems. And also, farmers commonly faced challenges as high cost for ICT usage, high price for ICTs tools, and poor ICT service. Besides, farmers’ other challenges were poor connectivity, inadequate support for the mother service provider, failure to attend the training, complexity to operate, and badly wanted news. Finally, this study recommended that farmers use effective utilization of ICTs in their farming in Nay Pyi Taw area that has the potential to make the rural communities prosperous as it enables the dissemination of required information in user-friendly patterns, easy to access, cost-effective ways at the right time with relevant information and training to be a skill.